Benefits and Advantages of Mediation - Tillaboyeva Muazzamoy (International Journal on Human-Computing Studies, 2021)
Mediation is a structured, interactive process where an impartial third party assists disputing parties in resolving conflict through the use of specialized communication and negotiation techniques. All participants in mediation are encouraged to actively participate in the process. Mediation is a "party-centered" process in that it is focused primarily upon the needs, rights, and interests of the parties. The mediator uses a wide variety of techniques to guide the process in a constructive direction and to help the parties find their optimal solution. Mediation, as used in law, is a form of alternative dispute resolution resolving disputes between two or more parties with concrete effects. Typically, a third party, the mediator, assists the parties to negotiate a settlement. Disputants may mediate disputes in a variety of domains, such as commercial, legal, diplomatic, workplace, community, and family matters.